Association between health-related physical fitness and academic performance in adolescents - Fábio Jorge Santos de Castro; Antonio Cesar Cabral de Oliveira (Universidade Federal de Santa Catarina, 2016)
This study aimed to verify the association between health-related physical fitness and academic performance in adolescents. Overall, 326 students aged 15-18 years of the Federal Institute of Sergipe (IFS) participated in this cross-sectional study. Data relating to physical fitness were collected by applying the following tests: body mass index, sit and reach, abdominal in one minute and one mile running, which comprise the American Alliance for Health, Physical Education, Recreation and Dance testing battery. Academic performance was measured by the grades of two-month period in the disciplines that comprise the following areas of knowledge: languages and codes, natural sciences and humanities, obtained from the IFS school record. Students with average grades ≥ 6.0 were considered on satisfactory academic performance. The prevalence of physical unfitness in the sample was 15.8% (girls 15.4%; boys 16.4%) in body composition, 32.3% (girls 23.1%; boys 41.5%) in flexibility, 93.0% (95.8% girls; 90.2% boys) in muscular strength and 86.9% (85.3% girls; 88.5% boys) in cardiorespiratory endurance. On academic performance, the prevalence of adolescents below the average grade was 8.8% (girls 5.6%; boys 12.0%) in languages and codes, 24.5% (girls 19.5%; boys 29.5%) in natural sciences and 12.8% (girls 11.9%; boys 13.7%) in humanities. Adolescents with low cardiorespiratory endurance levels were more likely to have worse academic performance (OR=2.39; CI95%=1.05 to 5.44). It was concluded that low cardiorespiratory endurance levels were associated with worse academic performance.